Gastrointestinal health anti-diarrheal mixture relieves spleen deficiency-induced diarrhea through regulating gut microbiota - Wu Zhengquan; Yao Liuyi; Guo Jun; Xu Zhong; Wang Zhengyan (Open Life Sciences)
This study evaluated the therapeutic efficacy of the gastrointestinal health anti-diarrheal mixture (GHAM) on diarrhea induced by spleen deficiency, focusing on its modulation of gut microbiota. Using specific pathogen-free Wistar rats, a spleen deficiency model was created through senna leaf gavage. Rats were divided into control, model, positive control, and GHAM treatment groups. After a 14-day treatment, fecal samples were analyzed via 16S rDNA sequencing to assess microbiota alterations. GHAM significantly mitigated diarrhea and enhanced food intake and fecal quality. It increased the abundance of beneficial bacteria, such as Romboutsia and Clostridium_sensu_stricto_1, and decreased the levels of diarrhea-associated bacteria, such as Prevotellaceae and Bacillus, thereby improving microbiota functionality. GHAM’s modulation of gut microbiota structure and function effectively alleviated spleen deficiency-induced diarrhea, positioning it as a potential natural herbal treatment for gastrointestinal ailments. This study lays the groundwork for further exploration of GHAM’s regulatory impact on gut health.